PENGARUH KEBIASAAN MENONTON DRAMA KOREA TERHADAP PERENCANAAN KARIR PESERTA DIDIK SMP NEGERI 14 PONTIANAK - Lqabilah, Lqabilah; Asrori, Muhammad; Yuline, Yuline (Universitas Tanjungpura, 2024)
This review expects to decide the impact of the propensity for watching Korean dramatizations on the vocation arranging of Grade VIII understudies at SMP Negeri 14 Pontianak. This study involves a quantitative methodology as relationship studies (interrelationship studies). The quantity of tests in this review were 31 respondents from an all-out populace of 294 understudies in class VIII A to VIII I. The information assortment method utilized was a circuitous correspondence strategy with an information assortment device as a poll which was disseminated straightforwardly to understudies. The consequences of the information examination in this study show that: (1) the propensity for watching Korean shows for class VIII understudies at SMP Negeri 14 Pontianak is in the high class, specifically 73.90%, (2) profession anticipating class VIII understudies at SMP Negeri 14 Pontianak has a level of 74.29% has a place with the high class, and (3) in light of exploration the propensity for watching Korean dramatizations impacts the vocation arranging of class VIII understudies of SMP Negeri 14 Pontianak. This is consistent with straightforward linear regression calculations, which yield the equation Y = 12.550 + 0.854X. The significance level that was achieved was 0.000 0.05%. This implies that Hâ‚ is acknowledged and Hâ‚€ is dismissed, so it is inferred that there is an impact between the propensity for watching Korean shows on the vocation arranging of Grade VIII understudies at SMP Negeri 14 Pontianak.